Determinação dos fluxos turbulentos de calor e momentum entre o oceano e a atmosfera na região sudoeste do oceano Atlântico - Santini, Marcelo Freitas (2017)
The knowledge about the mass and energy fluxes between the atmosphere and the ocean at different regions of the planet is of utmost importance for the improvement of the weather and climate predictions. This is mainly necessary in regions such as the South Atlantic Ocean where the formation and propagation of atmospheric transient systems like cyclones and cold fronts are frequent. For the realization of this study we used data collected during cruises onboard Brazilian research ships in the Southwestern Atlantic ocean in June 2012, October 2013 and October 2014. This work compares the sensible heat (H), latent heat (Le) and momentum (τ) fluxes between the ocean and the atmosphere, as well as the friction velocity (u∗) obtained from direct measurements using the Eddy Covariance Methodology (EC) with estimated obtained from the bulk turbulent parameterization. We describe and analyze the spatial and temporal differences for the period of the three cruises and their relation with local variables and processes, and with atmospheric effects at the large scale. The most significant differences are associated to regions where we observe intense SST gradients, intense differences between the air temperature (Tair) and SST, changes in the wind direction and the transition of synoptic systems. Friction velocity, important for forcing the oceanic currents and for its role on the turbulent fluxes determination, presented a good agreement between the two methods used here. The u∗ showed to be strongly dependent on the wind magnitude at the sea surface. Momentum fluxes also presented a good coherency between the two methods utilized, both on mean magnitudes and temporal variability. As expected, τ was dependent on the wind velocity, however temporal variations on its behavior were mainly associated to changes in the wind direction. Sensible heat flux presented a good agreement between the two methods, were bulk was able to reproduce in both magnitude and temporal variability the results obtained through CV. The H was mainly associated to the magnitude of the difference between SST and Tair. Latent heat flux presented significant differences between the two methods during the 2012 and 2013 experiments, performed at the southeastern coast of Brazil and at the Brazil- Malvinas Confluence (BMC) region, respectively. These differences were mostly associated to cold advection processes, high wind magnitudes and intense horizontal SST gradients. Nevertheless, during the 2013 experiment, the mean magnitudes of Le presented a good agreement, with the higher differences present at the BMC region. Considering that our study region is very dynamical at both spatial and temporal viewpoints, at the ocean and in the atmosphere, this work has demonstrated that in many situations the bulk parameterization does not represent the local reality. The present work allowed an advance in the present knowledge about the ocean-atmosphere interaction processes which have recognized importance for the weather and the climate of South America. Based upon the results of this work, future studies in the fields of numerical modeling of weather and climate, as well as general ocean circulation, may be improved.